Coping with the health condition from the perspective of people with HIV who abandoned treatment - Juliete Bispo dos Santos Mandu; Elen Ferraz Teston; Gleice Kelli Santana de Andrade; Sonia Silva Marcon (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to understand how people living with HIV who have abandoned treatment face their health condition. Methods: a qualitative study, based on the Chronic Care Model theoretical precepts. Data were collected between April and August 2021, through interviews with 24 people registered in a specialized service in the Brazilian Midwest. Results: coping with the health condition included good and bad moments and is influenced by individual behaviors and the way in which the network was organized. Treatment abandonment was motivated by the absence of signs and symptoms, the way care is provided and medication side effects. Final Considerations: care actions focusing on behavior change and maintenance become necessary in order to favor continuity of treatment. Furthermore, the gaps identified in the way health services are organized are subject to intervention.